2009
DOI: 10.1021/pr900257z
|View full text |Cite
|
Sign up to set email alerts
|

Selective Enrichment of Azide-Containing Peptides from Complex Mixtures

Abstract: A general method is described to sequester peptides containing azides from complex peptide mixtures, aimed at facilitating mass spectrometric analysis to study different aspects of proteome dynamics. The enrichment method is based on covalent capture of azide-containing peptides by the azide-reactive cyclooctyne (ARCO) resin and is demonstrated for two different applications. Enrichment of peptides derived from cytochrome c treated with the azide-containing cross-linker bis(succinimidyl)-3-azidomethyl glutarat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
84
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(87 citation statements)
references
References 45 publications
(105 reference statements)
2
84
1
Order By: Relevance
“…Thus, even if Anl were incorporated 10× more slowly at internal sites than at N-terminal sites, one would expect to detect comparable numbers of N-terminal and internal modifications. Consistent with this argument are the results of Nessen et al (50), who reported an analysis of peptides isolated from proteome-wide labeling in E. coli and found 10-fold more Aha modifications at internal sites than at N termini.…”
Section: Discussionsupporting
confidence: 64%
“…Thus, even if Anl were incorporated 10× more slowly at internal sites than at N-terminal sites, one would expect to detect comparable numbers of N-terminal and internal modifications. Consistent with this argument are the results of Nessen et al (50), who reported an analysis of peptides isolated from proteome-wide labeling in E. coli and found 10-fold more Aha modifications at internal sites than at N termini.…”
Section: Discussionsupporting
confidence: 64%
“…These include selective enrichment using affinity purification with biotinylated cross-linkers (15)(16)(17) and click chemistry with alkyne-tagged (18) or azide-tagged (19,20) cross-linkers. In addition, Staudinger ligation has recently been shown to be effective for selective enrichment of azidetagged cross-linked peptides (21).…”
Section: Dsso Contains Two Symmetric Collision-induced Dissociation (mentioning
confidence: 99%
“…In such cases, affinity purification of newly synthesized proteins has been recently facilitated by pulse labeling with noncanonical amino acids. Specifically, the replacement of methionine by its azide-bearing analog azidohomoalanine (AHA) allows the enrichment of newly synthesized proteins via click-chemistry using alkyne-functionalized beads (26,27). The combination of this enrichment approach with stable isotope labeling methods allows the quantitative analysis of proteome dynamics, providing insight into the regulation of protein synthesis (28).…”
mentioning
confidence: 99%